2008
DOI: 10.3340/jkns.2008.43.4.177
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing Factors Related to Shunt-Dependent Chronic Hydrocephalus after Aneurysmal Subarachnoid Hemorrhage

Abstract: Hydrocephalus after aneurysmal SAH seems to have a multifactorial etiology. Understanding predisposing factors related to the shunt-dependent chronic hydrocephalus may help to guide neurosurgeons for better treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 30 publications
3
51
1
4
Order By: Relevance
“…3,17,23 Previous studies have shown advanced age to be an independent risk factor for SDHCP after aSAH. 3,12,21,25,33 Our analysis demonstrated increased age to be associated with a higher risk of receiving a shunt after aSAH. van Gijn et al 9 have demonstrated a quantitative correlation between increasing age and higher bicaudate indices; therefore, it could be that hydrocephalus is diagnosed more frequently with increasing age.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…3,17,23 Previous studies have shown advanced age to be an independent risk factor for SDHCP after aSAH. 3,12,21,25,33 Our analysis demonstrated increased age to be associated with a higher risk of receiving a shunt after aSAH. van Gijn et al 9 have demonstrated a quantitative correlation between increasing age and higher bicaudate indices; therefore, it could be that hydrocephalus is diagnosed more frequently with increasing age.…”
Section: Discussionmentioning
confidence: 88%
“…It has been suggested that meningeal infection causes CSF flow disturbances, 4,17 ependymal cell dysfunction, and CSF barrier cell inflammation that lead to increased secretion of CSF 32 resulting in chronic hydrocephalus. It has been described that meningitis is associated with the duration of EVD, 33 as CSF sampling from EVD can increase the risk of meningitis. 34 Meningitis is a risk factor that could, in principle, be prevented with comprehensive management and therefore should be the focus of prevention efforts to minimize the patient's risk for shunting.…”
Section: Discussionmentioning
confidence: 99%
“…13 Large thirdventricle diameter (approximately 7 mm), high CSF protein levels, higher Hunt and Hess grade, and the presence of intraventricular blood have all been shown to be predictors of shunt dependency in patients with SAH who have developed hydrocephalus. 5,24 Post-SAH hydrocephalus is unique because of the variability in intracranial pressure (ICP).…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, it has been shown in patients with subarachnoid hemorrhage that malresorptive hydrocephalus may be caused by blood products clogging the arachnoid villi. 9,18 In this study, we sought to determine patient variables predicting the occurrence of true postoperative hydrocephalus.…”
mentioning
confidence: 99%